Thermal stability of dopants in boron carbide. (1st January 2022) - Du, Jun; Christian, Kent; Yang, Qirong; Hwang, Chawon; McAleer, Eoin; Haber, Richard A.
Abstract: Undoped (B4 C), B rich (B5.5 C), and B/Si co-doped (Si-B6.5 C) boron carbides were annealed at 500 °C for up to 21 days to investigate the thermal stability of primary dopants, B and Si. Structural changes associated with dedoping were investigated by X-ray diffraction (XRD) and Raman spectroscopy. The stable phase B4 C showed no microstructural or lattice parameter changes. Similarly, lattice parameters of B5.5 C remained constant, suggesting that B dopant is stable at the given conditions. However, the shortened lattice parameters and reduced Si content of Si-B6.5 C over the annealing time indicated that Si dopant was in a metastable state at the annealing temperature. Consequently, Si dedoping led to an increase in amorphization (a loss of local crystalline order) which degrades the ballistic performance of boron carbide. The insight highlights the importance of Si dopant in boron carbide and suggests that rapid processing may be necessary to retain more silicon for better performance. Graphical abstract: Image, graphical abstract